Pengaruh Kinerja Keuangan terhadap Corporate Social Responsibility (Studi Empiris pada Perusahaan Tambang yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2019) - R Muhammad Agung Nugraha; Sri Trisnaningsih (Universitas Batanghari, 2022)
Mining exercises are exercises that utilization regular resources unbounded so they can straightforwardly influence the environment around offshoots. As a type of hierarchical commitment towards results, partners should unveil the execution of Corporate Social Responsibility as per Law no. 40 of 2007 article 74. With the issuance of Corporate Social Responsibility (CSR) will change the general image of grounded members and can oversee execution related cash through benefits for providers and monetary accomplices will likewise be attracted to fair cash, this increment shows that associate worth is additionally developing . increment. This study expects to decide the profit from assets, return on abundance, and the general net installment of corporate social obligation with an assessment time of 3 years, 2017-2019. This review utilizes a quantitative methodology and tests completed by purposive testing strategies at mining partners. This study utilizes 60 data from the yearly reports of associates recorded on the Indonesia Stock Exchange. The testing and speculative testing system utilized in this test is by using the Statistical Product and Service Solutions (SPSS) 25 programming change.